Identification of the Degradation Products from α‐Tocopherol Used as Stabiliser in "Green" Propellants through its Lifetime. Issue 12 (26th October 2022) - Damseaux, Caroline; Scholl, Georges; Damblon, Christian; Dejeaifve, Alain; Dobson, Rowan; De Pauw, Edwin; Eppe, Gauthier
Abstract: Stabilisers are added to gun and rocket propellants to react with species responsible for nitrate ester degradation during storage. The degradation products can be toxic and therefore harmful. There is a need to replace such stabilisers by "green" molecules and to study their degradation patterns through ageing. Propellant powders must remain chemically stable for a minimum of ten years when stored at temperatures equivalent to 25 °C [1]. α‐Tocopherol is a natural product that has been known for decades in other fields (Vitamin E) such as the pharmaceutical, food and cosmetics industries. It can act as a 'green' stabiliser" for smokeless powders because its heat flow is stable over time. In this paper, we characterise its stabilisation mechanism by identifying its main degradation products that could form within the propellant in an oxidising environment and in the presence of nitric acid. Liquid chromatography (LC) and gas chromatography (GC) separations are performed in order to dissociate the compounds formed during ageing. Compounds are then analysed by APCI‐timsTOF to obtain the molecular ion masses and then perform fragmentation spectra (MS/MS) to characterise their structure. In addition, using preparative HPLC‐UV, the degradation products are collected and analysed by NMR, with the aim of identifying the molecules. These identification methods help to unravel the stabilisation mechanism under accelerated ageing conditions. A time‐related fluctuation of the degradation products amounts is also observed, which indicates that the decomposition products also have a stabilisation effect. The three major α‐tocopherol degradation products are identified as: 2, 3‐epoxy‐α‐tocopherylquinone, 5, 6‐epoxy‐α‐tocopherylquinone and α‐tocored. Abstract :